PENYALAHGUNAAN MEDIA SOSIAL SEBAGAI PENYEBAB PERCERAIAN DI PENGADILAN AGAMA MAJENE (KAJIAN FIKIH & MEDIA SOSIAL) - Djalaluddin, Muhammad Mawardi; Muhammad, Nuzha; Nurmadinah; Sakina (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
ABSTRACT Misuse of social media is one of the leading causes of divorce in the digital era. This research is aiming at determining the misuse of social media that causes divorce in the study of jurisprudence and social media. This research applies a qualitative descriptive type of research is sourced from interviews with judges at the Majene Religious Court, relevant books and articles. The results of the research show that social media is one of the platforms that causes a husband or wife to become nusyuz (disobedience) which can be shown by a change in the partner's attitude (infidelity) which then continues to become shiqaq which is a dispute between the couple, while in the study of social media, there is a relationship between cognitif dissonnance theory and virtual space that can cause divorce if the elements of attitude, perception and behaviour are not interconnected. This research provides to knowledge in relation to the impact of misuse of social media which results in divorce from a review of Islamic law and social media